Bloodlines : recovering Hitler's Nuremberg Laws; from Patton's trophy to public memorial - Platt, Anthony M. (Paradigm Publ, 2006)
Origins stories -- Present absences -- Tall like Germans -- Human betterment -- Blood and honor -- Hitler's signature -- Patton's trophy -- Outpost of civilization -- White man's burden -- Loot -- In limbo -- History lessons -- Past and present.